Incumplimiento del Principio de Acceso a la Educación en el Régimen Legal de la Educación Superior para su Ingreso - Gómez Samaniego, Víctor Hugo (2016)
In this thesis entitled "Breach of the Principle of Access to Education in the Legal System of Higher Education for Income", the issues raised goes to the right to education is found guaranteed in the Constitution of the Republic of Ecuador as a fundamental right guaranteed to all people to study at all levels. Thus the Article 26 of the Constitution provides. "Education.- Right to Education is a right of people throughout their lives and an unavoidable and inexcusable duty of the State. It is a priority area of public policy and state investment, guarantee equality and social inclusion and indispensable condition for the good life ". Article 3 of the General Regulation of the Organic Law on Higher Education provides: "The National Secretary of Higher Education, Science, Technology and Innovation, SENESCYT, implement the System Equalization and Admission to the income of high school graduates to higher education institutions public. Leveling System and Intake will have two components. The admission shall be considered permanent and stable a unified national system of registration, evaluation and allocation of quotas according to the merit of each student. The component leveling take into account the heterogeneity in training high school and / or characteristics of university careers”. On the other hand, the Organic Law on Higher Education in its Article 81 determines the System of Equalization and Admission: "The admission to institutions of public higher education will be regulated through the System of Equalization and Admission, which will be submitted all and aspiring students”. Here we identify that there is a contradiction between the Constitution of the Republic and the Organic Law on Higher Education, in the sense that the Constitution guarantees the right to applicants to access universities and pursue the career of choice, however the reality is different because it is limited this right and is forced to follow another career not related, which is given by the System Equalization and Admission. It is observed in the Constitution of the Republic which guarantees the right priority to the education of people, even allowing free access to education up to the third level, which contributes to the professional training of people. The leveling system and admission is causing serious inconvenience to the right to choose the race of applicants who wish to pursue at the Universities their free decision; rather this leveling system and admission rejects most students in the career they have chosen freely and imposes another race to be followed compulsorily thus has lost the freedom of university admissions and choose the race preferably student. Against this drawback aspiring first year, they are forced to follow their careers preferably in private universities that accept immediate, unimpeded, or rejections, but with cost. To fulfill this investigation we have taken the following criteria: To discuss free entry to higher education I must refer to the statement by Herman Jaramillo Ordóñez that freedom is the right of every individual of the human species to perform physical activities, intellectual and moral within the limits established by law. It is the possibility of choosing the exercise of rights and obligations. Legal inconsistencies in the Constitution and the Organic Law on Higher Education, according to Prieto Sanchís say the antinomy presupposes the existence of a contradiction between the statements deontic or regulatory qualifications established by two standards within the same system. The Importance of Higher Education for Bachilleres as Adam Smith says: The most prominent thinkers in the world, shares the view that education is not the top priority for the development of any society. Without it, nothing is possible. It allows the accumulation of knowledge by individuals and society. Education and learning of individuals are the basis of the wealth of nations. I have relied on the doctrine in the field of research concluding that the evaluation system and admission to high school graduates who provides the Organic Law on Higher Education, limiting admission to high school graduates and a specific career in higher education. With the foregoing it should be noted that the system of evaluation and admission provided the Organic Law on Higher Education and its General Regulations violates the right to access to higher education applicants, repeal still necessary, and allow the Law organic Higher education to be included as a requirement in Article 81, more than bachelor's degree, the certificate granted by the institution of secondary education have passed the leveling course and admission.